The Construction of Mathematical Communication Schemes Based on Learning Styles - Maulyda, Mohammad Archi; Erfan, Muhammad; Wulandari, Nourma Pramestie; HIdayati, Vivi Rachmatul; Umar, Umar (Indonesian Research Journal in Education |IRJE|, 2020)
The purpose of this study was to describe the construction of students’ mathematical communication in solving problems based on students’ learning styles. This research method is qualitative-descriptive. The subjects in this research were three students, each of these students are theoretical, reflective, and pragmatic learning styles. The research instrument used was mathematics problems with a topic similarity. The data obtained were in the form of students’ work and short unstructured interviews. The data were analyzed based on indicators of problem-solving and mathematical communication. The results showed that students with theoretical learning styles could communicate the entire process of the problem-solving well. Students with a reflective learning style could show a good problem-solving process. Even so, mathematical communication is not very clear. Students with a pragmatic learning style had a poor performance in solving problems. The mathematical communication is also not very good.